TERRA promotes telomerase‐mediated telomere elongation in Schizosaccharomyces pombe. (6th May 2016) - Moravec, Martin; Wischnewski, Harry; Bah, Amadou; Hu, Yan; Liu, Na; Lafranchi, Lorenzo; King, Megan C; Azzalin, Claus M
Abstract: Telomerase‐mediated telomere elongation provides cell populations with the ability to proliferate indefinitely. Telomerase is capable of recognizing and extending the shortest telomeres in cells; nevertheless, how this mechanism is executed remains unclear. Here, we show that, in the fission yeast Schizosaccharomyces pombe, shortened telomeres are highly transcribed into the evolutionarily conserved long noncoding RNA TERRA. A fraction of TERRA produced upon telomere shortening is polyadenylated and largely devoid of telomeric repeats, and furthermore, telomerase physically interacts with this polyadenylated TERRA in vivo . We also show that experimentally enhanced transcription of a manipulated telomere promotes its association with telomerase and concomitant elongation. Our data represent the first direct evidence that TERRA stimulates telomerase recruitment and activity at chromosome ends in an organism with human‐like telomeres. Synopsis: In S. pombe, shortened telomeres produce elevated levels of the lncRNA TERRA, which associates with telomerase and promotes telomerase recruitment and telomere elongation in cis. This is the first direct evidence that TERRA is a positive regulator of telomerase in an organism with human‐like telomeres. Shortened telomeres produce elevated levels of the TERRA lncRNA in S. pombe . Polyadenylated TERRA molecules largely devoid of telomeric repeats interact with telomerase. Experimentally induced telomere transcription leads to telomerase‐mediated telomere elongation in cis. Abstract : In S. pombe, shortened telomeres produce elevated levels of the lncRNA TERRA, which associates with telomerase and promotes telomerase recruitment and telomere elongation in cis. This is the first direct evidence that TERRA is a positive regulator of telomerase in an organism with human‐like telomeres.